Intravenous Magnesium Sulphate as an Adjuvant Therapy for Acute Exacerbations of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Taimur Farid; Abdousamad Said Omar; Sijah Varar Kandi; Soja Puthiyara Maliyekal; Tze Quan Tuen; Amrutha Thazhuthedath Vijayan; Lakshmi Sudhir Pillai; Ahmed Talaat Deiab; Muhammad Sajid; Ahmad Mesmar; Eman Ibrahim Elzain Hassan; Rijas Keethadath; et al. (Life, 2025)
Background: Intravenous magnesium sulfate (IV MgSO4) may serve as an effective adjunct therapy to improve clinical outcomes in patients experiencing acute exacerbations of chronic obstructive pulmonary disease (AECOPDs). Methods: A comprehensive search was conducted on PubMed, Cochrane, and EMBASE from inception to April 2025 to find eligible studies comparing IV MgSO4 plus standard treatment versus standard treatment alone. A random-effects meta-analysis was conducted using RevMan. Results: Nine studies (seven RCTs and two observational studies) met the inclusion criteria. Pooled analysis demonstrated that adjunctive IV MgSO4 significantly improved peak expiratory flow rate at 45 min (MD = 18.50, 95% CI = 6.36 to 30.65) and significantly reduced hospital admission rates from the emergency department (OR = 0.45, 95% CI = 0.23 to 0.88). No significant differences were observed in the length of hospital stay (MD = −0.83, 95% CI = −2.99 to 1.33) and adverse events (OR = 0.79, 95% CI = 0.20 to 3.13; p = 0.73, I2 = 25%) between the two groups. Conclusions: Adjunct MgSO4 in AECOPD is associated with significant improvement in peak expiratory flow rate at 45 min and reduced hospitalization rates. Additional large-scale, multicenter randomized controlled trials are needed to validate and strengthen these findings.